Spring Data ji shu shou ce = Spring Data : modern data access for enterprise Java / = Spring Data : modern data access for enterprise Java - Pollack, Mark; Gierke, Oliver; Risberg, Thomas; Brisbin, Jon; Hunger, Michael (GoTop Information, Inc., 2013)
Detailed summary in vernacular field.